Child Psychology and Childhood Education: A Cognitive-Developmental View by Lawrence Kohlberg with Rheta DeVries, Greta Fein, Daniel Hart, Rochelle Mayer, Gil Noam, John Snarey, and James Wertsch, Reviewed by Sara Sullivan - Sullivan, Sara (Analytic Teaching, 2014)
Introduction: In the preface to Child Psychology and Childhood Education: A Cognitive-Developmental View, Lawrence Kohlberg describes the "paradigm shift" characteristic of child development and education during the past 20 years. Both fields have experienced a dramatically changed perspective as a result of American awareness of Jean Piaget's theory of cognitive development. The shift to a Piagetian perspective has been evident in the domains of social and emotional development, as well as in that of cognitive development. It has, moreover, generated a great deal of developmental research and provided a theoretical rationale for a number of early education programs. In spite of the widespread popularity of this cognitive-developmental model among both child psychologists and educators, neither its relationship to other developmental theories nor its implications for educational practices have been fully explored.